Dampak Pemahaman Keagamaan dan Kemampuan Literasi Media Terhadap Sebaran Berita Hoax di Komunitas Surabaya Mengaji - Ellyda Retpitasari (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2022)
The research analysis is related to the influence of religious understanding and media literacy skills on the tendency to spread hoax news in the Surabaya Mengaji Community. This study uses a quantitative research approach, with a population of participants in the Sunday routine study at the Jami Mecca Bendul Merisi Mosque in Surabaya under the auspices of the Surabaya Mengaji Community. for statistical data analysis using the Yule's Q statistical formula. Based on the results of Yule's Q statistical calculations it shows that the correlation of religious understanding to the spread of hoax news is -0.178, which means it has a "low negative relationship", the correlation of media literacy skills to the spread of hoax news reaches -0.431 which can be interpreted as having a "moderate negative relationship", and the correlation of religious understanding and media literacy skills to the spread of hoax news, is tested through explanation, this is because in this study Qxy Tied T is smaller than zero order, -0.552 as Qxy Tied T, and -0.748 as zero order, and the difference is more than 0.10. So it can be analyzed that religious understanding and media literacy skills still have an important and meaningful relationship.